Saluran, Marjin, dan Efisiensi Pemasaran Jamur Tiram di Kota Denpasar - FATURACHMAN, BINTANG; ANTARA, MADE; WIBAWA, MADE SATRIA (Jurnal Agribisnis dan Agrowisata (Journal of Agribusiness and Agritourism); Vol.13, No.1, November 2024, 2024)
Channels, Margin, and Marketing Eficiency of Oyster Mushroom in Denpasar City. Oyster mushrooms are a non-seasonal horticultural commodity that can be relied upon in the Denpasar city and can be cultivated because they require a narrow planting medium, thus having a high level of productivity. There is a price gap between what farmers receive and what end consumers pay. The purpose of this research to analyze the marketing channels of oyster mushroom carried out by farmers and marketing institutions in the Denpasar city, as well as to analyze marketing efficiency based on marketing margins and farmer's share. The quantitative data of this study include marketing efficiency, marketing margins, and farmer's share. Qualitative data in this study include marketing channel patterns. The respondents in this study were 25 people, farmers. The sample of this study was determined by the method of saturated sampling for oyster mushroom farmers, while marketing institutions were determined using snowball sampling. The results showed that the marketing patterns consisted of three marketing, consissting of (I) farmers - consumers, (II) farmers - retailers - consumers, and (III) farmers - restaurants - consumers. In marketing channel I, the marketing margin is Rp 0 and the farmer's share is 100%. In marketing channel II, the marketing margin is Rp 12,000 and the farmer's share is 62.5%. In marketing channel III, the marketing margin is Rp 66,000 and the farmer's share is 23.2%. Based on the calculation of efficiency values, different efficiency values were obtained where the efficiency value of marketing channel I is 0%, marketing channel II is 11.7%, and marketing channel III is 36.5% .Oyster mushroom farmers should prioritize distributing oyster mushrooms through channel II to become the most efficient marketing channel to gain higher profits.